Bootstrapping the Primitive Recursive Functions by 47 Colors - Riis, Søren (BRICS Report Series, 1994)
I construct a concrete coloring of the 3 element subsets of N. It has the property that each homogeneous set s_0, s_1, s_2, ..., s_r, r >= s_0 - 1 has its elements spread so much apart that F_omega(s_i) < s_i+1 for i = 1, 2, ..., r -1. It uses only 47 colors. This is more economical than the approximately 160000 colors used by Ketonen and Solovay.